Screening and characterization of bioactive compounds from two epiphytic microlichen and evaluation of their in vitro antioxidant activity - Shubham Pradhan; Satyabrata Dash; Bijayananda Sahoo; Sabyasachy Parida; Biswajit Rath (SpringerOpen, 2024)
Abstract Background Lichens in symbiosis produce a wide range of primary and secondary fine compounds in extreme environmental conditions that have a broad range of biological properties as well as antioxidant potential and can be used in future pharmaceuticals as a natural source of antioxidant molecules. Results The two microlichen species collected are identified based on morphological and molecular techniques; further studies are carried out by analyzing phytochemicals (FTIR, GC MS), and antioxidant assays are evaluated. The non-enzymatic antioxidant activity is evaluated by DPPH and FRAP assays. The methanol extract of both lichens showed virtuous DPPH scavenge with IC50 of P. nitida (125.76 ± 0.023 µg/ml) and G. scripta IC50 (176.90 ± 0.058 µg/ml). FRAP activity was prominent in the methalonic extract. The enzymatic antioxidant activity is observed by SOD and catalase activity. The cytosolic (Cu-Zn-SOD and Fe-SOD) and mitochondrial SOD (Mn-SOD) are detected in lichens, though P. nitida shows mitochondrial Mn-SOD and cytosolic Cu-Zn-SOD and Fe-SOD, whereas G. scripta has a single cytosolic Cu-Zn-SOD; however, two isoforms of catalase were reported. GC-MS analysis screened bioactive metabolites such as phenols, Quinons, heterocyclic compounds, benzofurans, fatty acids, pyrans, carboxylic acid, aliphatic aldehydes, organic alcohol, fluorinated aliphatic substances, ketones, terpenes and fatty alcohols in P. nitida, whereas, in G. scripta screened fatty acids, alcohols, hydrocarbons, carbonyl compounds, polyols, terpenes, glycosides, phenols, and sugar alcohols detected in the chromatogram peak. FTIR analysis revealed functional groups like Alcohols, Amines, Amides, Alkanes, Aldehydes, Carboxylic acid, Alkynes, Esters, Ketones, Anhydrides, Acid chlorides, Alkenes, Aromatic compounds, Nitro compounds, Alkyl and Aryl Halides in both lichens. Conclusions The results obtained in the present study proved that P. nitida and G. scripta have promising antioxidant activity owing to the presence of polyphenols and terpenes, as evidenced by DPPH and FRAP assay along with enzymatic analysis (SOD and CAT). Thus both the lichens may be used as natural sources of new bioactive molecules having pharmaceutical interest.